Effect of fear of missing out on learning burnout in medical students: a moderated mediation - Ye, Xin; Li, Yang; Liu, Yang; Zheng, Qiuyue; Lin, Zhongli; Zeng, Yinhua; Lin, Ziyue; Zhu, Tan; Chen, Xiayan; Chen, Liangliang; Liu, Tao (Frontiers in Psychiatry, 2023)
Introduction Learning burnout has a significant negative impact on students’ academic performance and professional development, which has been exacerbated by the growing trend of problematic smartphone use, such as smartphone addiction, among young people. Recently, the literature on excessive social media use has revealed a critical role of fear of missing out. Objective The purpose of this study was to examine how fear of missing out affects smartphone addiction and its subsequent effect on learning burnout in college students. Methods In Study 1, 352 medical students were recruited to complete a cross-sectional survey. In Study 2, 2,948 college students were recruited to complete a cross-sectional survey. Further in Study 3, 30 medical students were recruited into a mindfulness-based intervention program. Results Study 1 preliminarily confirmed that fear of missing out was positively correlated with learning burnout. Study 2 then revealed a moderated mediation model showing that fear of missing out may increase smartphone addiction, which in turn affects their sleep quality and finally leads to learning burnout. This chain mediation model was moderated by the participants’ level of mindfulness. To confirm the promoting role of mindfulness, Study 3 further confirmed that mindfulness training indeed can improve smartphone addiction and reduce learning burnout in medical students. Discussion Theoretical and practical contributions were discussed, highlighting the effects of fear of missing out on smartphone addiction and a moderating role of mindfulness training.